2018
DOI: 10.2174/1573397113666170329123308
|View full text |Cite
|
Sign up to set email alerts
|

The Limitations of Gram-stain Microscopy of Synovial Fluid in Concomitant Septic and Crystal Arthritis

Abstract: The incidence of concurrent septic and crystal arthritis may be higher than previously thought. Synovial fluid samples in concomitant septic and crystal arthritis are significantly less likely to have a positive Gram-stain at microscopy than in cases of an isolated septic arthritis. We would advise the clinician to maintain a high index of suspicion for septic arthritis in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The CpG DNA can bind to Toll-like receptor 9 (TLR9) in immune cells, leading to the production of cytokines such as IL-1β, TNF, IL-6 and IL-12 [ 62 , 63 ]. Some studies showed that intra-articular injection of S. aureus CpG DNA can induce arthritis in mice [ 64 , 65 ].…”
Section: Septic Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…The CpG DNA can bind to Toll-like receptor 9 (TLR9) in immune cells, leading to the production of cytokines such as IL-1β, TNF, IL-6 and IL-12 [ 62 , 63 ]. Some studies showed that intra-articular injection of S. aureus CpG DNA can induce arthritis in mice [ 64 , 65 ].…”
Section: Septic Arthritismentioning
confidence: 99%
“…Antibiotic therapy is started ideally after synovial fluid samples have been obtained [ 64 ]. Gram stains of synovial fluid are helpful when positive, but they are not always sensitive enough for the diagnosis of septic arthritis [ 65 ]. Patients should be treated empirically for septic arthritis when synovial fluid leukocyte counts exceed 50,000 cells/mm 3 , although gout and pseudogout also commonly present with leukocyte counts of this magnitude [ 66 ].…”
Section: Diagnosis and Treatment Of Septic Arthritismentioning
confidence: 99%
“…Si elle reste une étape essentielle pour l'identification du pathogène, la mise en culture du liquide synovial est une démarche longue qui retarde l'instauration d'une antibiothérapie ciblée (10). La coloration de Gram est une méthode rapide mais qui présente une sensibilité limitée pour détecter l'infection bactérienne, à savoir d'environ 45 à 50 % (4,(11)(12)(13). La culture du liquide synovial peut être négative dans 20 % des cas et nécessite un délai pouvant aller jusqu'à 72 heures.…”
Section: Introductionunclassified
“…Even though they are the essential means to identify a pathogen, synovial fluid cultures are time-consuming and consequently targeted antibiotic treatment are delayed(10). Gram staining is a fast, but not very efficient method with only 45 to 50% of sensitivity to detect bacterial infection (4,(11)(12)(13). The synovial fluid culture can be negative in 20% of cases, and can take up to 72 hours.…”
Section: Introductionmentioning
confidence: 99%